The Influencer of Authenticity Attributes and Celebrity Congruence on Purchase Intention: The Mediating Role of Parasocial Relationship - Tsuraya, Aisya; Ridanasti, Erlita (Dinasti Publisher, 2026)
This study examines the influence of authenticity attributes and celebrity congruence on purchase intention through parasocial relationship. The purpose of this research is to understand how influencer characteristics and perceived congruence shape emotional attachment and influence consumer purchase intention in the context of self-branding. This study adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Data were collected through an online questionnaire from 299 respondents who follow Sashfir and have been exposed to Lafiye promotional content. The findings indicate that expertise, truthful endorsement, and uniqueness have a positive and significant effect on purchase intention, while sincerity and visibility do not show significant effects. Celebrity congruence has a positive and significant effect on purchase intention. Furthermore, authenticity attributes and celebrity congruence significantly influence parasocial relationship, which in turn significantly affects purchase intention. These findings highlight the importance of emotional bonds between influencers and audiences in driving consumer behavior.